Membongkar Makna di Balik Iklan Layanan Masyarakat tentang Makanan Ultra-Proses: Analisis Semiotika Roland Barthes - Aliyah, Sa'adatul; Dida, Susanne; Lusiana, Elnovani (Balai Bahasa Sulawesi Selatan, 2025)
This study aims to analyze the construction of the ultra-processed food narrative ideology in the BBC News Indonesia public service announcement on YouTube Shorts titled